Fostering Connection in the Classroom: Emotional Intelligence and Its Influence on Teacher-Student Dynamics - Parajuli, Gaurav; Singh, Sagar; Phuyal, Aryan; Pant, Sivansh (DAV Research Journal, 2025)
The paper investigates contribution of emotional intelligence towards the quality of teacher-student dynamics, with a specific focus on mediating role of teacher commitment and the contextual influence of school culture. The research utilized non-probability convenience sampling technique to gather data from 232 respondents within a descriptive and causal research framework. Based on El theory, the research employed a five-point Likert scale to measure the variables. Hypothesis were tested using regression modeling and correlation analysis. The research discovered that Emotional Intelligence plays a crucial role in enhancing the quality of teacher-student relationships. Teachers who are emotionally aware, empathetic, and skilled in regulating their feelings are more capable of fostering trust, open communication, and emotional security in the classroom. Emotional intelligence not only enables better classroom management but also strengthens relational bonds that are vital for student development and learning. The research is valuable for practical implications in educational institutions and teacher development programs. The strong positive relationship between emotional intelligence and teacher-student relationships suggests that teacher training programs should integrate emotional intelligence development as a core component. Training teachers to be more self-aware, empathetic, and emotionally responsive can lead to more meaningful interactions with students and foster classroom environments that support emotional and academic growth. This study provides a novel contribution by integrating emotional intelligence, teacher commitment, and school culture into a single framework to understand their combined impact on teacher-student relationships. This paper offers new insights particularly relevant to school environments in Nepal, where such comprehensive relational studies are limited. The findings aim to inform both educational policy and teacher training practices to enhance relational dynamics in classrooms.